Universal Design for Learning University Challenges - Kobuladze, Nato (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
The modern global world, the changed natural and ecological conditions, have accelerated changes in various spheres of life, including the educational system. It has become necessary to search for new pedagogical approaches and innovations, to create diverse educational technologies that ensure overcoming the challenges that modernity offers us. In this paper, based on observation and documentary research methods, the university challenges of universal design of teaching at the Akaki Tsereteli State University are studied. During the research, the causes of the problem were identified, and accordingly, the University's Continuing Education Center planned a number of events, including training courses and seminars to eliminate the problem. Our research process analyzed training documentation, including quantitative and qualitative data, training materials, applicant feedback and responses. The results of the study showed that we can overcome these challenges by implementing universal design principles and technologies in classroom teaching, using adaptive technical means and educational resources, raising awareness, establishing centers for psychological support for students, and constantly searching for innovations and innovations, expanding access to university education.